Technical efficiency evaluation: study on Malaysian electrical and electronics firms - Abdullah, Mohd Fahmy; Lai, Wei Sieng; Muhammad Isa, Hamdan (2019)
The purpose of this study is to measure the level of technical efficiency (TE) and to analyse the factors of technical inefficiency of electrical and electronic manufacturing industry in Malaysia in 2015. The determinants studied include capital-labour ratio, education level ratio, firm size, information technology, and communication expenses, training expenditure, wage rates, and research and development expenditure. This study uses data on 531 firms based on the latest census of 2015 obtained from the Department of Statistics, Malaysia using the Stochastic Frontier Analysis (SFA) approach. Based on the results, the firm’s overall TE level is high at 0.836. For the determinants of TE, it was found that firm size can reduce the inefficiencies of firm, while capital-labour ratios shows a positive relationship with technical inefficiencies in firms. The policy implication is that the electrical and electronic manufacturing industry needs to focus on scale economic achievement and high technology production in line with the competency level of employee and create more international industry technical cooperation.